Technology foresight - more than fashion?. (1st January 2001) - Peissl, Walter
Technology foresight is blooming all around the western industrialised countries. Is it more than fashion? What are the benefits for S&T policy? This introduction gives an overview of the special issue of the International Journal of Technology Management. In the first part, you will find a discussion of some theoretical basics of the political decision process, to which technology foresight is supposed to deliver input, and of some methodological questions of technology foresight. In the second part, the main focus is laid on the analysis of technology foresight activities on different levels. These analyses are based upon empirical results from recently finished foresight activities. Finally, in the third part, a spotlight is thrown on "Seven Paradoxes" of foresight in a rather provoking form, which seems to be a good starting point for further discussions.